Chondrosesamoidean ligament enthesopathy: Prevalence and findings in a population of lame horses imaged with positron emission tomography. (29th June 2020) - Norvall, Amy; Spriet, Mathieu; Espinosa, Pablo; Ariño‐Estrada, Gerard; Murphy, Brian G.; Katzman, Scott A.; Galuppo, Larry D.
Abstract: Background: Increased 18 F‐Sodium Fluoride ( 18 F‐NaF) uptake at the chondrosesamoidean ligament (ChSL) attachment on the distal phalanx was identified in an exploratory positron emission tomography (PET) study. The prevalence and significance of this lesion has not been previously investigated. Objectives: The goal of this study was to assess the prevalence of this lesion, its association with other imaging findings and with clinical signs. Study design: Retrospective cross‐sectional analytical study. Methods: All horses with 18 F‐NaF PET and computed tomography (CT) imaging of the feet performed between October 2016 and December 2017 were included in the study. All PET scans were independently assessed by two radiologists for increased uptake at the ChSL attachment site and concurrent imaging was reviewed. Clinical findings, treatment and outcome were retrieved from the medical records. Results: Fourteen of 30 horses (20/56 feet) had increased 18 F‐NaF uptake in the region of interest. ChSL enthesopathy was the primary lesion in three horses. Other PET abnormalities included navicular bone uptake (13 feet) and ipsilateral palmar process uptake (9 feet). There was no significant association between ChSL enthesopathy and other lesions. ChSL enthesopathy was significantly associated with foot lameness. CT abnormalities at the ChSL attachment were initially identified in one foot, and retrospectively noted in another five following the results of PET imaging. Main limitations: The study is retrospective and there was a limited sample size. Conclusions: PET led to identification of ChSL enthesopathy in a large proportion of horses with foot pain. This finding is most commonly associated with other lesions but may also represent the main abnormality. The axial border of the palmar processes of the distal phalanx should be carefully assessed on cross sectional imaging to identify this lesion. ChSL enthesopathy may be an important but previously not recognised component of foot pathology in horses.